The burden of carbon monoxide poisoning in China from 1990 to 2021 and forecasts to 2050 - Yanwu Yu; Jinzhou Yu; Ding Yuan; Fang Yang; Hongyi Yan; Pin Jiang; Mengnan Guo; Zhigao Xu; Gaiqin Yan; Yan Zhang; Yanxia Gao (Frontiers in Public Health)
AimThis study aimed to analyze the disease burden of carbon monoxide poisoning (COP) in China from 1990 to 2021 and to forecast future trends.MethodsData were retrieved from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. The incidence, prevalence, mortality, and Disability Adjusted Life Years (DALYs) and their corresponding Age-Standardized Rates (ASRs) were examined to assess the burden of COP in China from 1990 to 2021. The Joinpoint regression model was used to investigate the trend changes of COP burden. The Age-Period-Cohort model was employed to delineate age, period, and cohort effects on the trends in disease burden. The Bayesian Age-Period-Cohort analysis method was applied to predict the changing trends of COP disease burden in China from 2022 to 2050.ResultsIn 2021, there were 152,820 incidences COP in China, with an Age-Standardized Incidence Rate (ASIR) of 13.06 per 100,000 population. There were 13,289 fatalities, corresponding to an Age-Standardized Mortality Rate (ASMR) of 0.8 per 100,000 population. The total DALYs amounted to 499,528, with an Age-Standardized DALY Rate (ASDR) of 35.02 per 100,000 population. The peak burden, as measured by DALYs, was observed in the 30–34 age group. Trend analysis employing Joinpoint regression revealed an initial increase in ASIR and Age-Standardized Prevalence Rate (ASPR) until 2015, followed by a subsequent decline. Moreover, the ASMR and ASDR showed fluctuant downward trends. Predictions from the Bayesian Age-Period-Cohort model suggest that the incidence, prevalence, mortality, and DALYs of COP in China are expected to increase from 2022 to 2050, peaking in 2038, while the ASRs are projected to decline.ConclusionFrom 1990 to 2021, China experienced dynamic temporal patterns in the burden of COP, characterized by an initial rise in incidence and prevalence, followed by a decline in recent years, alongside a general downward trajectory in mortality and DALYs. Additionally, projections indicate a potential resurgence in COP-related burden in the coming decades.